Otolaryngology in Medical Education: Hands-on Training at an SRFC Community Site Improves Medical Student Knowledge and Skills - Abigail Groszkiewicz; Hemchandra Patel; Joseph Walden; Benjamin Dreskin; Adam McCann; Raisa Tikhtman; Joseph Kiesler; Megan Rich (Journal of Student-Run Clinics, 2024)
Background: There are known otolaryngology education gaps and exposure inequalities in existing medical school curricula. It has been shown that students participating in otolaryngology instruction sessions emerge with increased knowledge and confidence in skills. The population our student-run free clinic serves is high-risk for head and neck cancers, and evidence has shown that clinical exams are a very effective tool for early detection of these lesions. In this study, our clinic offered head and neck cancer screening events to meet community needs as well as student training nights to meet student education needs.Methods: Medical students of all training levels were invited to participate. Participating students first completed a pre-training interests and skills assessment survey and a knowledge test. Students then attended a training night led by otolaryngology residents that included an educational lecture and hands-on skills practice. Afterwards, students re-took the knowledge test. One week later, students participated in the live screening event at the clinic. Afterwards, students completed another interest and skills assessment survey.Results: Sixty students attended our three student training nights. Pre-participation (n=53), 52.5% of students were interested in otolaryngology as a specialty, most students felt little to no confidence in performing a general head and neck exam (66%) or taking a head and neck cancer history (81%), and the average knowledge test score was 58% correct. The post-training (n=41) average knowledge test score increased to 78.3% correct, a statistically significant increase (p < 0.001). Post-event participation (n=20), most students reported increased interest in otolaryngology (75%), and improved confidence in performing an exam (95%) and taking a history (95%).Conclusions: Participation in our student training night and head and neck cancer screening event increased students’ interest in otolaryngology as a specialty, their confidence in otolaryngology physical exam skills and their knowledge about head and neck cancer.